Reverse logistics of agrochemical packaging: a contribution to achieving the goals of Sustainable Development Objectives - Michalovicz, Emilim; Beuren, Fernanda Hänsch; Fagundes, Alexandre Borges; Vaz, Caroline Rodrigues; Vieira, Cleide; Kobs, Fábio Fernando (Revista Caribeña de Ciências Sociales, 2025)
THIS IS AN ARTICLE PUBLISHED BY Revista Caribeña de Ciências Sociales (e-ISSN: 2254-7630) ON 2025-03-18, AVAILABLE ONLINE: https://doi.org/10.55905/rcssv14n3-010 Abstract This research aims to examine the presence of the Sustainable Development Goals within the reverse logistics system of agrochemical packaging across three grain cooperatives located in northern Santa Catarina. A literature review was conducted to explore the concepts and historical milestones of sustainability, as well as the evolution of sustainable development goals. This process enabled the selection of goals that support the reverse supply chain of agrochemical packaging. After comparing these goals with the reverse logistics process, it was necessary to observe whether the sustainable development objectives are being practically followed. By administering a questionnaire and analyzing each response, it was found that the practices aligned with these goals are being implemented. This required examining statements that indicated relationships between the goals. Therefore, it is concluded that the study is valid for investigating the integration of sustainable development objectives into the daily routines of workers and farmers in the region, as well as for providing insights into learning processes and access to information related to the reverse supply chain activities associated with these goals.
Keywords: Reverse Logistics; Sustainable Development; Pesticide Packaging; Sustainable Development Goals